2011
DOI: 10.1016/j.ajpath.2010.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Pigment Epithelium-Derived Factor Inhibits Left Ventricular Remodeling and Improves Cardiac Function in Rats with Acute Myocardial Infarction

Abstract: Oxidative stress and inflammation are involved in cardiac remodeling after acute myocardial infarction (AMI). We have found that pigment epithelium-derived factor (PEDF) inhibits vascular inflammation through its anti-oxidative properties. However, effects of PEDF on cardiac remodeling after AMI remain unknown. We investigated whether PEDF could inhibit left ventricular remodeling and improve cardiac function in rats with AMI. AMI was induced in 8-weekold Sprague-Dawley rats by ligation of the left ascending c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 38 publications
2
24
1
Order By: Relevance
“…20 However, in pancreatitis responses, the early fibrosis seen in PEDF-null mice suggests that PEDF serves as a counterregulatory mechanism in pancreatitis. This function is also consistent with recently published data 8,10,18,19 on PEDF's antifibrotic role in the kidney, liver, heart, and eye. PEDF overexpression in a transgenic mouse model ameliorated the increase in TGF-␤1 and inflammatory markers in an eye injury model associated with neovascularization and fibrosis.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…20 However, in pancreatitis responses, the early fibrosis seen in PEDF-null mice suggests that PEDF serves as a counterregulatory mechanism in pancreatitis. This function is also consistent with recently published data 8,10,18,19 on PEDF's antifibrotic role in the kidney, liver, heart, and eye. PEDF overexpression in a transgenic mouse model ameliorated the increase in TGF-␤1 and inflammatory markers in an eye injury model associated with neovascularization and fibrosis.…”
Section: Discussionsupporting
confidence: 93%
“…8 Similarly, in a model of acute myocardial infarction, PEDF infusion reduced cardiac fibrosis through down-regulation of TGF-␤1 and fibrillar collagen expression, thereby improving left ventricular ejection. 18 These in vivo studies support earlier cellular studies that identified PEDF as a quiescence factor for fibroblasts.…”
supporting
confidence: 84%
See 3 more Smart Citations